The Effect of Macromedia Flash-based Animation Media on the Discovery Learning Model on the Learning Outcomes of Class XI Science Students of SMAN 5 Makassar - Almur, Faathir; Agussalim, Hastuti; Nur, Andi Bulqiah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
The Effect of Animation Media based on Macromedia Flash in Discovery Learning Model Toward Students Learning Outcomes in Class XI IPA SMA Negeri 5 Makassar (Study on Buffer Solution). Thesis. Study of Chemistry Education. Chemisty Department. Faculty of Mathematics and Science. State University of Makassar (Supervised by Taty Sulastry and Sudding). This research was quasi experiment research that aimed to know the effect of animation media based on macromedia flash in discovery learning model toward students learning outcomes in class XI IPA SMA Negeri 5 Makassar study on buffer solution. The research design was posttest only control group design. The population of this research was students in class XI IPA SMA Negeri 5 Makassar that consist of eight classes. Sampling was conducted by random sampling. The experimental group was XI IPA 1 and the control group was XI IPA 2. The average of learning outcomes of experimental group was 80,86 higher than the control group was 63,69. Inferential statistic analysis toward students learning outcomes showed that data on the experimental group and the control group were homogeneous but not normally distributed so hypothesis testing using non parametric test by Mann-Whitney with ∝ = 0,05 obtained Zcount>Ztable (5,56 >1,64). It shows there was an effect of animation media based on macromedia flash in discovery learning model toward students learning outcomes in class XI IPA SMA Negeri 5 Makassar on subject matter of buffer solution.